KARAKTERISTIK SPASIAL DAERAH PENENTU TERJADINYA STUNTING DI SUMATERA SELATAN : Karakteristik Spasial Daerah Penentu Terjadinya Stunting di Sumatera Selatan - Ahmad Sadiq; Susyani Susyani; Fatmalina Febry; Indah Purnama Sari; Sartono Sartono; Indah Margarethy; Tanwirotun Ni’mah (Universitas Airlangga, 2023)
Background: The prevalence of stunting in Indonesia is 24.4%. The determinants of stunting are family, household, inadequate nutritional intake, exclusive breastfeeding, infectious diseases and social factors. Stunting has an impact on cognitive development, chronic disease, mental retardation and obesity. Objectives: To identify the determinants of stunting at the district/city level in South Sumatra. Methods: Cross-sectional study design. The number of samples is 2,272 respondents. Data on stunting under-fives in 17 regencies/cities comes from Riskesdas 2018. Regency/city characteristic variables include swamp areas, malaria endemic, gross domestic product (LPDB), population growth rate (LPP) and the Public Health Development Index (IPKM). Data analysis was carried out using univariate, bivariate with chi-square, and identifying the most influential factors with multivariate analysis. Results: The number of respondents is 2,272 toddlers; the prevalence of stunting is 31.2%. 52.5% of Regencies/cities in South Sumatra are swamp areas. The significant characteristic variable with stunting is the type of swamp area p=0.001 PR=1.230 (1.088-1.390 95% CI). The multivariate result of the variable that has the greatest influence on the incidence of stunting is the swamp area variable p = 0.000. Results; PR 1.469 (95% CI 1.208-1.788). Regencies with non-swamp type areas had a 1.469 times higher risk of having stunting toddlers compared to swampy area type. Conclusions: The prevalence of stunting is 31.2%. A significant variable with the occurrence of stunting wass the condition of the swamp area, p=0.001, OR = 1.230 (1.088-1.390). The multivariate results of the most dominant factor were swamp areas PR value: 1.469, Regencies with non-swamp type areas had a 1.469 times higher risk of having stunting toddlers compared to swampy area type regencies after control with API, IPKM and LPP variables (95% CI: 1.208 - 1.788).